Reconstructing Junggringan Kawruh Jiwa as a Psychospiritual Approach Based on Javanese Local Wisdom in Overcoming Academic Pressure on Vocational School Students from Broken Homes - Uswatun Marhamah; Mungin Edy Wibowo; Sugiyo Sugiyo; Heru Mugiarso (Nadwa: Jurnal Pendidikan Islam, 2025)
The goal of this research is to investigate Junggringan Kawruh Jiwa, a psychospiritual approach grounded in Javanese local wisdom, and its effects on the academic pressure faced by Vocational High School (SMK) students from disadvantaged backgrounds. Data for this study were collected using qualitative methods with a case study design. It included in-depth interviews, participatory observation, and documentation. The study findings show that the use of knowledge on the edge of psychic is practical for students to use in managing academic anxiety in three main ways: (1) daily reflection rituals: students meditate and breathe, raising their own awareness while at the same time dispersing symptoms of stress; (2) context learning: students employ Javanese philosophical values such as memayu hayuning bawana and urip mung mampir ngombe as a framework to see academic pressure as a part of the inner maturation process; and (3) emotional mentoring from teachers who serve as surrogate parents provides students with psychological support and a place for them to express their emotions outright. Student respondents were generally positive about the program, showing increased openness, decreased anxiety, and increased self-belief, despite initial resistance. The contribution of this research lies in its complementing school guidance and counseling with a whole-school, local cultural approach. It likewise offers sustainable, context-based models of psychospiritual intervention for students from low-income family backgrounds.